Phytochemicals of Peat land Sauropus androgynus Leaves and Their Potential Use in Improving Performance of Broiler Chickens - Sandriya, Ardi; Noorrahman, Nabil Fariz; Astuti, Maria Haryulin; Paulini, Paulini; Anjalani, Ria (Jurnal Veteriner, 2025)
This study aims to determine the content of secondary metabolites in katuk ( Sauropus androgynus L. Merr. ) leaves growing in peatlands through phytochemical tests. The ethanol extract of katuk ( Sauropus androgynus L. Merr. ) leaves obtained from peatlands was subjected to phytochemical screening, revealing the presence of secondary metabolites such as flavonoids, alkaloids, phenol, saponins, tannins, terpenoids, and steroids. This content has different results from the ethanol extract of katuk leaves from mineral soil. The organoleptic test results demonstrated that the ethanol extract obtained from katuk leaves originating from peatlands had a thick form, the distinctive smell of katuk leaves, a bitter taste, a brown colour, an ash content of 7.56 ± 0.87, and a mass loss of 3.82 ± 1.49. This result is the same as the ethanol extract of katuk leaves from mineral soil. All the ingredients in the ethanol extract of katuk leaves from peatlands can enhance the productivity of broiler chickens. It can be concluded that the type of soil where the plant grows influences the results of its secondary metabolites and the findings from the analysis of the phytochemical content in the extraction of katuk leaves originating from peatlands are different from katuk leaf extract originating from mineral soil.